Ligand- and Structure-Based Virtual Screening Identifies New Inhibitors of the Interaction of the SARS-CoV-2 Spike Protein with the ACE2 Host Receptor - Timoteo Delgado-Maldonado; Alonzo González-González; Adriana Moreno-Rodríguez; Virgilio Bocanegra-García; Ana Verónica Martinez-Vazquez; Erick de Jesús de Luna-Santillana; Gerard Pujadas; Guadalupe Rojas-Verde; Edgar E. Lara-Ramírez; Gildardo Rivera (MDPI AG, 2024)
The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is a fast-spreading viral pathogen and poses a serious threat to human health. New SARS-CoV-2 variants have been arising worldwide; therefore, is necessary to explore more therapeutic options. The interaction of the viral spike (S) protein with the angiotensin-converting enzyme 2 (ACE2) host receptor is an attractive drug target to prevent the infection via the inhibition of virus cell entry. In this study, Ligand- and Structure-Based Virtual Screening (LBVS and SBVS) was performed to propose potential inhibitors capable of blocking the S receptor-binding domain (RBD) and ACE2 interaction. The best five lead compounds were confirmed as inhibitors through ELISA-based enzyme assays. The docking studies and molecular dynamic (MD) simulations of the selected compounds maintained the molecular interaction and stability (RMSD fluctuations less than 5 Å) with key residues of the S protein. The compounds DRI-1, DRI-2, DRI-3, DRI-4, and DRI-5 efficiently block the interaction between the SARS-CoV-2 spike protein and receptor ACE2 (from 69.90 to 99.65% of inhibition) at 50 µM. The most potent inhibitors were DRI-2 (IC50 = 8.8 µM) and DRI-3 (IC50 = 2.1 µM) and have an acceptable profile of cytotoxicity (CC50 > 90 µM). Therefore, these compounds could be good candidates for further SARS-CoV-2 preclinical experiments.